Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By forming rock salt-type, spinel-type and layered rock salt-type structures on the surface of secondary particles of lithium transition metal composite oxide, the capacity reduction of lithium transition metal composite oxide with high Ni content is solved during the charge and discharge cycle. and the problem of rising conduction resistance achieves the high energy density and excellent cycling characteristics of the battery.
Patent Information
- Application Number
- CN202380049064.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-09
- Publication Date
- 2025-02-11
AI Technical Summary
Lithium transition metal composite oxides with high Ni content are prone to decreased capacity and increased conductivity resistance during the charge and discharge cycle, which affects the cycle characteristics and energy density of the battery.
Using a positive electrode active material made of lithium transition metal composite oxide containing at least Ni, the secondary particles of the composite oxide form a rock salt type, spinel type and layered rock salt type structure, through the lamination combination of these structures Stabilize the particle surface and inhibit the growth of the NiO phase.
It effectively suppresses the reduction of the capacity of the positive electrode active substance during charging and discharging, improves the circulation characteristics and energy density of the battery, and makes the circulation characteristics of the battery excellent and the energy density high.
Smart Images

Figure CN119422261A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery using the positive electrode active material. Background Art
[0002] In recent years, lithium transition metal composite oxides with high Ni content have attracted much attention as positive electrode active materials with high energy density. However, lithium transition metal composite oxides with high Ni content have the following problems: the surface structure of composite oxide particles is easily unstable, and the capacity decreases greatly during long-term charge and discharge cycles.
[0003] In view of the above situation, Patent Document 1 proposes a positive electrode active material having a composition formula of LiNi x Mn y Co z O 2 As shown, it includes a core particle having a layered rock salt structure with a space group R-3m and a covering layer having a spinel structure covering the core particle. Patent document 1 describes the following effect: by using this positive electrode active material, the capacity reduction of the positive electrode active material and the increase of the conductive resistance can be suppressed.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-9562 Summary of the invention
[0007] As mentioned above, when using a lithium transition metal composite oxide with a high Ni content as a positive electrode active material for a non-aqueous electrolyte secondary battery, it is an important topic to suppress the capacity reduction accompanied by charge and discharge and improve the cycle characteristics (durability). It should be noted that the results of the research of the present inventors, etc. show that when the positive electrode active material of patent document 1 is used, the initial capacity of the battery decreases. That is, it is expected that the lithium transition metal composite oxide with a high Ni content is a high energy density, but in the positive electrode active material of patent document 1, it becomes lost.
[0008] The positive electrode active material for a non-aqueous electrolyte secondary battery disclosed herein comprises a lithium transition metal composite oxide containing at least Ni, and the lithium transition metal composite oxide is a secondary particle formed by aggregation of primary particles, and the primary particles present on the surface of the secondary particles have a crystal structure, and the crystal structure comprises a rock salt type structure, a spinel type structure and a layered rock salt type structure formed in sequence from the particle surface.
[0009] The nonaqueous electrolyte secondary battery of the present disclosure includes a positive electrode including the positive electrode active material, a negative electrode, and a nonaqueous electrolyte.
[0010] The positive electrode active material disclosed in the present invention is a high energy density positive electrode active material with a high Ni content, and suppresses the capacity reduction accompanying the charge and discharge of the non-aqueous electrolyte secondary battery, and improves the cycle characteristics. The non-aqueous electrolyte secondary battery using the positive electrode active material disclosed in the present invention has high energy density and excellent cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a diagram schematically showing an axial cross section of a nonaqueous electrolyte secondary battery (cylindrical battery) as an example of an embodiment.
[0012] Figure 2 This is a diagram schematically showing a cross section of a positive electrode active material particle as an example of an embodiment.
[0013] Figure 3 The figure schematically shows the crystal structure of the surface of particles of a positive electrode active material and its vicinity observed by a transmission electron microscope. DETAILED DESCRIPTION
[0014] As mentioned above, when using a lithium transition metal composite oxide with a high Ni content as a positive electrode active material, there is a problem that the capacity decreases during long-term charge and discharge cycles. It is believed that the major factor is that the particle surface structure of the positive electrode active material becomes unstable with charge and discharge, and the crystal structure of the particle surface shifts to the NiO phase of the rock salt structure and grows. In addition, the diffusion of Li ions is hindered by the NiO phase, resulting in an increase in resistance and a decrease in capacity.
[0015] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that: in the primary particles on the surface of the secondary particles of the positive electrode active material (lithium transition metal composite oxide containing Ni), a rock salt structure, a spinel structure and a layered rock salt structure are formed in sequence from the particle surface, thereby specifically improving the cycle characteristics. The spinel structure is generated as the lower layer of the NiO phase of the rock salt structure, so that the growth of the NiO phase is suppressed, and as a result, it is believed that the capacity reduction associated with charge and discharge is efficiently suppressed.
[0016] In order to achieve both high energy density and good cycle characteristics, it is considered that a stacked structure of a rock salt type structure and a spinel type structure is essential as the surface layer of the primary particles present on the surface of the secondary particles.
[0017] Hereinafter, an embodiment of the positive electrode active material and the non-aqueous electrolyte secondary battery using the positive electrode active material of the present disclosure will be described in detail with reference to the accompanying drawings. It should be noted that the configuration formed by selectively combining the constituent elements of the multiple embodiments and modified examples described below is included in the scope of the present disclosure.
[0018] Hereinafter, a cylindrical battery in which a wound electrode body 14 is housed in a bottomed cylindrical outer shell can 16 is exemplified as a non-aqueous electrolyte secondary battery, but the outer shell of the battery is not limited to a cylindrical outer shell can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer shell can, a coin-shaped battery having a coin-shaped outer shell can, or a pouch-type battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.
[0019] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 comprises: a wound electrode body 14, a nonaqueous electrolyte (not shown) and a can 16 for accommodating the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 has a positive electrode 11, a negative electrode 12 and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the can 16 is blocked by a sealing body 17. In the following, for the convenience of explanation, the sealing body 17 side of the battery is set as the upper side, and the can bottom side of the can 16 is set as the lower side.
[0020] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. Examples of the non-aqueous solvent include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof. The non-aqueous solvent may also contain a halogen-substituted product (e.g., fluoroethylene carbonate, etc.) obtained by replacing at least a portion of the hydrogen atoms of these solvents with halogen atoms such as fluorine. Examples of the electrolyte salt include LiPF 6 In addition, vinylene carbonate (VC) may be added in an amount of 5% by mass or less relative to the mass of the non-aqueous electrolyte.
[0021] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by being spirally wound. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0022] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0023] A gasket 28 is provided between the outer shell can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed in the outer shell can 16, in which a part of the side surface is bulged inwardly and is used to support the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer shell can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer shell can 16 by the groove portion 22 and the open end of the outer shell can 16 that is pressed and connected to the sealing body 17.
[0024] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0025] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , and in particular, the positive electrode active material constituting the positive electrode 11 will be described in detail.
[0026] [positive electrode]
[0027] The positive electrode 11 has a positive electrode core and a positive electrode composite material layer disposed on the surface of the positive electrode core. The positive electrode core may include a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, and the like. The positive electrode composite material layer includes a positive electrode active material, a binding material, and a conductive material, and is preferably disposed on both sides of the positive electrode core except for the portion to which the positive electrode lead 20 is connected. The positive electrode 11 can be manufactured, for example, as follows: a positive electrode composite material slurry including a positive electrode active material, a binding material, and a conductive material is applied to the surface of the positive electrode core, and after the coating is dried, it is compressed to form a positive electrode composite material layer on both sides of the positive electrode core, thereby being manufactured.
[0028] As the conductive material contained in the positive electrode composite material layer, carbon black such as acetylene black, ketjen black, graphite, carbon nanotube (CNT), carbon nanofiber, graphene and other carbon materials can be exemplified. As the binding material contained in the positive electrode composite material layer, fluorine-containing resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.
[0029] The positive electrode 11 contains a lithium transition metal oxide containing at least Ni. Hereinafter, for the sake of convenience, the lithium transition metal composite oxide is referred to as "composite oxide (Z)". The composite oxide (Z) functions as a positive electrode active material. The positive electrode active material has the composite oxide (Z) as a main component, or may be substantially composed of only the composite oxide (Z). It should be noted that the positive electrode active material may contain composite oxides other than the composite oxide (Z) or other compounds within the scope of not impairing the purpose of the present disclosure.
[0030] The composite oxide (Z) contains 80 mol% or more of Ni relative to the total molar number of metal elements other than Li. By making the content of Ni 80 mol% or more, a battery with high energy density is obtained. The content of Ni relative to the total molar number of metal elements other than Li may be 85 mol% or more, or may be 90 mol% or more. The upper limit of the content of Ni is, for example, 95 mol%.
[0031] The composite oxide (Z) preferably further contains at least one selected from Mn and Co. As an example of a suitable composite oxide (Z), a lithium transition metal composite oxide containing Ni, Co and Al, a lithium transition metal composite oxide containing Ni, Co and Mn, and a lithium transition metal composite oxide containing Ni and Mn can be cited. When the composite oxide (Z) contains Co, the content of Co is preferably 2 to 7 mol% relative to the total molar number of metal elements other than Li. In this case, the material cost is suppressed, and a battery with high capacity and excellent cycle characteristics is easily realized.
[0032] When the composite oxide (Z) contains Mn, the content of Mn is preferably 2 to 15 mol% relative to the total molar number of metal elements other than Li. When the content of Ni is 90 mol% or more, the content of Mn is, for example, 2 to 10 mol%. In this case, battery performance such as capacity and cycle characteristics can be improved more efficiently. When the composite oxide (Z) contains Al, the content of Al is preferably 1 to 5 mol% relative to the total molar number of metal elements other than Li. In this case, high capacity can be ensured, the stability of the crystal structure can be improved, and the cycle characteristics can be improved more efficiently.
[0033] The composite oxide (Z) preferably further contains at least one selected from Ca and Sr. For example, the composite oxide (Z) has a composition formula of Li a Ni b Co c Mn d Al e Ca f Sr g O h (wherein, 0.8≤a≤1.2, 0.80≤b<1, 0≤c≤0.07, 0≤d≤0.10, 0≤e≤0.05, 0≤f≤0.01, 0≤g≤0.01, 1≤h≤2, b+c+d+e+f+g=1). When the composite oxide (Z) contains at least one selected from Ca and Sr, the effect of improving the cycle characteristics becomes more significant.
[0034] In the composite oxide (Z), the content of Ca and Sr is, for example, 1 mol% or less relative to the total molar number of metal elements other than Li. When the composite oxide (Z) contains Ca and Sr, their total is preferably 1 mol% or less. In this case, the cycle characteristics can be efficiently improved without causing undesirable conditions such as an increase in resistance and a decrease in capacity. Ca and Sr are effective even in very small amounts, but the lower limit of their content is preferably 0.05 mol%. The total content of Ca and Sr is preferably 0.05 to 1 mol%, more preferably 0.1 to 0.5 mol%, relative to the total molar number of metal elements other than Li.
[0035] At least one selected from Ca and Sr is present at the interface between primary particles, for example, at least inside the secondary particles of the composite oxide (Z). In this case, it is believed that the inhibitory effect of side reactions becomes obvious, and the cycle characteristics can be efficiently improved. Ca and Sr present at the interface of the primary particles can be confirmed by TEM-EDX and STEM-EDX. At least one selected from Ca and Sr is present at the interface between each primary particle, for example, in a dispersed state without omission. It should be noted that it can also be attached to the surface of these secondary particles.
[0036] The composite oxide (Z) may contain elements other than Li, Ni, Mn, Co, Al, Ca and Sr. As an example of the element, Nb, Zr, Ti, W, Si, B, Mg, Fe, Cu, Na, K, Ba, Mo and the like can be cited. The content of the elements constituting the composite oxide (Z) can be measured using an inductively coupled plasma emission spectrophotometer (ICP-AES), an electron probe microanalyzer (EPMA), or an energy dispersive X-ray analyzer (EDX).
[0037] Figure 2 FIG. 2 is a diagram schematically showing a cross section of a particle of a composite oxide (Z). Figure 2 As shown, the composite oxide (Z) is a secondary particle 30 formed by the aggregation of a plurality of primary particles 31. The volume-based median particle size (D50) of the composite oxide (Z) is, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm. The composite oxide (Z) is a secondary particle 30 formed by the aggregation of primary particles 31, and therefore, the D50 of the composite oxide refers to the D50 of the secondary particle 30.
[0038] D50 is the particle size at which the cumulative frequency of the smallest particle size in the volume-based particle size distribution is 50%, and is also called the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by MicrotracBEL Corp.) using water as a dispersion medium.
[0039] The average particle size of the primary particles 31 is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles 31 is calculated by averaging the diameter of the circumscribed circle of the primary particles 31 extracted from the analysis of the scanning electron microscope (SEM) image of the cross section of the secondary particles 30. Prescribed pores may exist inside the secondary particles 30. The pores exist, for example, at the interface between the primary particles 31. The average porosity of the secondary particles 30 is, for example, 0.1 to 5%. The porosity of the secondary particles 30 is the ratio of the area of the pores to the cross section of the secondary particles, and is calculated according to the formula: (area of the pores / cross-sectional area of the secondary particles) × 100.
[0040] The porosity of the secondary particles 30 is obtained by analyzing the SEM image of the cross section of the secondary particles. Regarding the extraction of the primary particles 31 and the pore area, it is appropriate to select image analysis software such as Image J, Avizo-Materials Science, etc. to perform the extraction. The SEM image is subjected to noise removal by non local means filter, BM3D, etc., and the threshold of the overlapping brightness is used for edge detection and MarkerBased-Watershed method to extract the primary particles 31 and the pore area. It should be noted that the area detected according to Watershed is defined as the primary particle, and the low brightness area is defined as the pore, with the high brightness value area as the center.
[0041] Figure 3 Schematic diagram of the surface of the composite oxide (Z) particles and their vicinity observed by a transmission electron microscope (TEM, STEM) Figure 2 The crystal structure in the micro region of the composite oxide (Z) can be analyzed by the nanobeam electron diffraction method using TEM. Figure 3 , an electron diffraction spectrum of a nanobeam present in the vicinity of the surface of the primary particle 31 on the surface of the secondary particle 30 is schematically shown.
[0042] like Figure 3 As shown, the primary particle 31 existing on the surface of the secondary particle 30 contains three crystal phases. The primary particle 31 existing on the surface of the secondary particle 30 has a crystal structure, and the crystal structure includes a rock salt type structure, a spinel type structure and a layered rock salt type structure formed in sequence from the particle surface. That is, within a predetermined depth range (hereinafter sometimes referred to as the "surface layer") from the surface of the primary particle 31, a three-phase structure with different crystal structures is formed. The three-phase structure can be formed in the surface layer of the primary particle 31 existing on the surface of the secondary particle 30, and can also be formed in the surface layer of the primary particle 31 connected to the internal pores of the secondary particle 30.
[0043] The crystal structure of the composite oxide (Z) is as follows: For example, most of the surface layer of the primary particle 31 existing on the surface of the secondary particle 30 and the surface layer of the primary particle 31 connected to the internal pores are layered rock salt type structures. The layered rock salt type structure is a layered crystal structure in which transition metal ions and Li ions are alternately arranged, and belongs to the space group R-3m. Li ions can move smoothly in the layered rock salt type structure.
[0044] In the present embodiment, as described above, a rock salt type structure and a spinel type structure are formed only on the surface layer of the primary particle 31 existing on the surface of the secondary particle 30 and on the surface layer of the primary particle 31 connected to the internal pores of the secondary particle 30. The rock salt type structure is considered to be a crystalline phase derived from the NiO phase generated on the surface of the particle and belongs to the space group Fm-3m. The rock salt type structure is different from the layered rock salt type structure and hinders the diffusion of Li ions. The spinel type structure belongs to the space group Fd-3m.
[0045] The average thickness of the rock salt type structure is preferably less than 5nm, more preferably less than 4nm, and particularly preferably less than 3nm. If the average thickness of the rock salt type structure is within this range, the improvement effect of the cycle characteristics becomes more obvious. It should be noted that the average thickness of the rock salt type structure refers to the average value of the shortest distance from any position on the particle surface to the interface with the spinel type structure in the cross section of the primary particle 31, and can be analyzed based on the nanobeam electron diffraction method using TEM. The lower limit of the average thickness of the rock salt type structure is not particularly limited, and as an example, it is 0.5nm.
[0046] The rock salt type structure is formed only within a thickness range of 5 nm, particularly preferably 3 nm, from the surface of a specific primary particle 31. When the rock salt type structure is formed within this range, it is considered that the effect of the spinel type structure existing on the inner side of the particle is compared with the rock salt type structure. The rock salt type structure is formed before the battery is charged and discharged.
[0047] The average thickness of the spinel structure is preferably less than 7nm, more preferably less than 6nm, and particularly preferably less than 5nm. If the average thickness of the spinel structure is within this range, the improvement effect of the cycle characteristics becomes more obvious. It should be noted that the average thickness of the spinel structure refers to the average value of the shortest distance from the interface with the rock salt structure to the interface with the layered rock salt structure in the cross section of the primary particle 31, and can be analyzed based on the nanobeam electron diffraction method using TEM. The lower limit of the average thickness of the spinel structure is not particularly limited, and as an example, it is 1.5nm.
[0048] The spinel structure is preferably formed after charging and discharging and does not exist before charging and discharging of the battery. The above-mentioned average thickness of the spinel structure is, for example, a value after a cycle test described later. That is, a three-phase structure of a rock salt structure, a spinel structure, and a layered rock salt structure is generated as the battery is charged and discharged, and after the same charge and discharge cycle as the cycle test described later, a spinel structure of the above thickness is formed. The results of the research conducted by the present inventors show that whether a spinel structure is formed depends on the synthesis method of the positive electrode active material. That is, a composite oxide (Z) that generates a spinel structure after charging and discharging and a composite oxide that does not generate a spinel structure can be separately produced.
[0049] The composite oxide (Z) can be synthesized, for example, by mixing and calcining a transition metal oxide containing Ni, Mn, Co, Al, etc., a Ca raw material, a Sr raw material, and a Li raw material such as lithium hydroxide (LiOH). The calcined product is crushed and then washed with water to obtain the composite oxide (Z). As an example of the Ca raw material, Ca(OH) 2 , CaO, CaCO 3 、CaSO 4 、Ca(NO 3 ) 2 As an example of Sr raw material, Sr(OH) 2 、Sr(OH) 2 ·H 2 O、Sr(OH) 2 8H 2 O, SrO, SrCO 3 、SrSO 4 、Sr(NO 3 ) 2 wait.
[0050] In terms of forming the above-mentioned three crystalline phases on the surface of the primary particle 31, the molar ratio (Li / Me ratio) of Li in the Li raw material to the metal element (Me) in the composite oxide and the sintering conditions are particularly important factors and must be strictly controlled. The suitable Li / Me ratio also varies slightly depending on the composition of the mixture, but as an example, it is 1.015 to 1.055. For example, when the Li / Me ratio is too low, such as 1.000, the mixing increases without forming a spinel structure. On the other hand, when the Li / Me ratio is too high, such as 1.060, the crystal growth is excessively advanced, and rapid rock salt structuring proceeds without forming a spinel structure.
[0051] The calcining process of the above-mentioned mixture, for example, includes a first calcining process and a second calcining process at a higher temperature than the first calcining process. In addition, the calcining of the mixture is carried out in an oxygen atmosphere, but it is preferred to set the oxygen concentration to 85% or more. For example, when the oxygen concentration is too low such as below 80%, the oxygen defects increase, and the spinel structure is not formed. The suitable first calcining temperature also slightly varies depending on the composition of the mixture, but as an example, it is 600 to 680°C. The suitable second calcining temperature is, for example, 700 to 780°C. If the calcining temperature is too high, the crystal growth is excessively advanced, and rapid rock salt structuring proceeds, and the spinel structure is not formed.
[0052] The calcining process is carried out by putting the above mixture into a calcining furnace. The first heating rate from room temperature to the first calcining temperature is preferably 2 to 4°C / minute. In addition, the heating rate from the first calcining temperature to the second calcining temperature is preferably slower than the first heating rate. If the heating rate is too fast, oxygen defects, strain in the structure, etc. remain, and the spinel structure is not formed.
[0053] [negative electrode]
[0054] The negative electrode 12 has a negative electrode core and a negative electrode composite material layer disposed on the surface of the negative electrode core. The negative electrode core may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film of the metal disposed on the surface. The negative electrode composite material layer includes a negative electrode active material and a binding material, and is preferably disposed on both sides of the negative electrode core except for the portion to which the negative electrode lead 21 is connected. The negative electrode 12 can be manufactured, for example, as follows: a negative electrode composite material slurry including a negative electrode active material and a binding material is applied to the surface of the negative electrode core, and after the coating is dried, it is compressed to form a negative electrode composite material layer on both sides of the negative electrode core, thereby being manufactured.
[0055] The negative electrode composite material layer generally contains a carbon material that reversibly absorbs and releases lithium ions as a negative electrode active material. A suitable example of a carbon material is natural graphite such as flaky graphite, block graphite, and earthy graphite, block artificial graphite (MAG), and artificial graphite such as graphitized mesophase carbon microbeads (MCMB). In addition, as a negative electrode active material, an active material containing at least one of an element such as Si, Sn, etc. that alloys with Li, and a material containing the element can be used. A suitable example of the active material is a SiO 2 The negative electrode active material may be a Si-containing material in which Si particles are dispersed in a silicate phase such as a lithium silicate phase or an amorphous carbon phase. Graphite and the Si-containing material may also be used together as the negative electrode active material.
[0056] The binder contained in the negative electrode composite material layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode 11, but preferably styrene-butadiene rubber (SBR) is used. In addition, the negative electrode composite material layer preferably further comprises CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, SBR is suitably used in combination with CMC or its salt, PAA or its salt.
[0057] [Separator]
[0058] A porous sheet having ion permeability and insulation is used in the separator 13. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. As the material of the separator 13, suitable materials are polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 13 may have a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin may be formed on the surface of the separator 13.
[0059] A filler layer containing an inorganic filler may be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.
[0060] Example
[0061] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.
[0062] <Example A1>
[0063] [Synthesis of lithium transition metal composite oxide (positive electrode active material)]
[0064] The composite oxide containing Ni, Co, and Al is mixed with lithium hydroxide in such a way that the molar ratio (Li / Me ratio) of Li in lithium hydroxide to the metal element (Me) in the composite oxide is 1:1.020. The mixture is put into a calcining furnace and calcined in two stages. In the calcining process, the mixture is calcined under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was heated at a rate of 2 mL / min and a flow rate of 5 L / min per kg of the mixture), and the temperature was raised from room temperature to 650°C (hereinafter referred to as the "first sintering temperature") at a heating rate of 3°C / min (hereinafter referred to as the "first heating rate"). Thereafter, the temperature was raised from 650°C to 750°C (hereinafter referred to as the "second sintering temperature") at a heating rate of 1°C / min (hereinafter referred to as the "second heating rate"), and maintained at 750°C for 3 hours. The sintered product was crushed and washed with water to obtain a lithium transition metal composite oxide (positive electrode active material).
[0065] The lithium transition metal composite oxide was analyzed by ICP-AES, and the composition of the composite oxide was confirmed to be Li 0.99 Ni 0.90 Co 0.05 Al 0.05 O 2In addition, from the SEM image of the lithium transition metal composite oxide, it was confirmed that the composite oxide was a secondary particle formed by aggregation of primary particles.
[0066] [Production of positive electrode]
[0067] The above-mentioned lithium transition metal composite oxide is used as a positive electrode active material. The positive electrode active material is mixed with acetylene black and polyvinylidene fluoride (PVdF) at a solid content mass ratio of 95:3:2, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode composite material slurry. The positive electrode composite material slurry is applied to both sides of a positive electrode core formed by aluminum foil, and after the coating film is dried, the coating film is rolled with a roller and cut into a specified electrode size to obtain a positive electrode having a positive electrode composite material layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed from the surface of the positive electrode core is provided on a part of the positive electrode.
[0068] [Production of negative electrode]
[0069] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with a dispersion of sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) at a solid content mass ratio of 100:1:1, and water is used as a dispersion medium to prepare a negative electrode composite material slurry. The negative electrode composite material slurry is applied to both sides of a negative electrode core formed of copper foil, and after the coating film is dried, the coating film is rolled with a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode composite material layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a portion of the negative electrode.
[0070] [Preparation of non-aqueous electrolyte]
[0071] LiPF 6 The precipitate was dissolved at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) at a volume ratio of 3:3:4 (25° C.) to prepare a non-aqueous electrolyte solution.
[0072] [Fabrication of test battery cell (non-aqueous electrolyte secondary battery)]
[0073] An aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode, and the positive electrode and the negative electrode are wound into a spiral shape with a polyolefin separator interposed therebetween to prepare a wound electrode body. The electrode body is housed in a bottomed cylindrical outer can, and after the nonaqueous electrolyte is injected, the opening of the outer can is blocked with a sealing body to obtain a test battery cell.
[0074] <Example A2>
[0075] A lithium transition metal composite oxide was synthesized in the same manner as in Example A1 except that the second calcination temperature was changed to 730° C., and a test battery cell was produced using the composite oxide as a positive electrode active material.
[0076] <Example A3>
[0077] Calcium hydroxide was further added as a raw material of lithium transition metal composite oxide. A lithium transition metal composite oxide was synthesized in the same manner as in Example A1, and the composite oxide was used as a positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.887 Co 0.04 Al 0.05 Ca 0.023 O 2 .
[0078] <Example A4>
[0079] A lithium transition metal composite oxide was synthesized in the same manner as in Example A1 except that strontium hydroxide was further added as a raw material of the lithium transition metal composite oxide. The composite oxide was used as the positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.899 Co 0.05 Al 0.05 Sr 0.01 O 2 .
[0080] <Example A5>
[0081] Calcium hydroxide and strontium hydroxide were further added as raw materials for lithium transition metal composite oxide. The lithium transition metal composite oxide was synthesized in the same manner as in Example A1, and the composite oxide was used as the positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.877 Co 0.05 Al 0.04 Ca 0.023 Sr 0.01 O 2 .
[0082] <Comparative Example A1>
[0083] A lithium transition metal composite oxide was synthesized in the same manner as in Example A1 except that the first heating rate was changed to 5°C / min and the second heating rate was changed to 3°C / min, and a test battery cell was prepared using the composite oxide as a positive electrode active material.
[0084] <Comparative Example A2>
[0085] A lithium transition metal composite oxide was synthesized in the same manner as in Example A1 except that the oxygen concentration in the calcination step was changed to 80%, and a test battery cell was prepared using the composite oxide as a positive electrode active material.
[0086] <Comparative Example A3>
[0087] A lithium transition metal composite oxide was synthesized in the same manner as in Example A1 except that the second calcination temperature was changed to 800° C., and a test battery cell was produced using the composite oxide as a positive electrode active material.
[0088] <Comparative Example A4>
[0089] A lithium transition metal composite oxide was synthesized in the same manner as in Example A1 except that the Li / Me ratio was changed to 1.000, and a test battery cell was produced using the composite oxide as a positive electrode active material.
[0090] <Comparative Example A5>
[0091] A lithium transition metal composite oxide was synthesized in the same manner as in Example A1 except that the Li / Me ratio was changed to 1.060 and the second calcination temperature was changed to 800° C. The composite oxide was used as a positive electrode active material to produce a test battery cell.
[0092] <Example B1>
[0093] [Synthesis of lithium transition metal composite oxide (positive electrode active material)]
[0094] The composite oxide containing Ni, Co, and Mn is mixed with lithium hydroxide in such a way that the molar ratio (Li / Me ratio) of Li in lithium hydroxide to the metal element (Me) in the composite oxide is 1:1.050. The mixture is put into a calcining furnace and calcined in two stages. In the calcining process, the mixture is calcined under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The first heating rate was 3°C / min, and the temperature was raised from room temperature to 630°C (the first calcination temperature). Thereafter, the second heating rate was 1°C / min, and the temperature was raised from 630°C to 770°C (the second calcination temperature), and maintained at 770°C for 5 hours. The calcined product was crushed and washed with water to obtain a lithium transition metal composite oxide (positive electrode active material).
[0095] The lithium transition metal composite oxide was analyzed by ICP-AES, and the composition of the composite oxide was confirmed to be Li 0.99 Ni0.90 Co 0.05 Mn 0.05 O 2 In addition, from the SEM image of the lithium transition metal composite oxide, it was confirmed that the composite oxide was a secondary particle formed by aggregation of primary particles.
[0096] <Example B2>
[0097] A lithium transition metal composite oxide was synthesized in the same manner as in Example B1 except that the Li / Me ratio was changed to 1.030 and the retention time of the second calcination temperature was changed to 8 hours, and a test battery cell was prepared using the composite oxide as a positive electrode active material.
[0098] <Example B3>
[0099] Calcium hydroxide was further added as a raw material of lithium transition metal composite oxide. A lithium transition metal composite oxide was synthesized in the same manner as in Example B1, and the composite oxide was used as a positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.89 Co 0.05 Mn 0.04 Ca 0.02 O 2 .
[0100] <Example B4>
[0101] Calcium hydroxide and strontium hydroxide were further added as raw materials for lithium transition metal composite oxide. The lithium transition metal composite oxide was synthesized in the same manner as in Example B1, and the composite oxide was used as the positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.885 Co 0.04 Mn 0.04 Ca 0.03 Sr 0.005 O 2 .
[0102] <Comparative Example B1>
[0103] The first heating rate was changed to 5°C / min, the second heating rate was changed to 3°C / min, and the second sintering temperature was changed to 750°C. In addition, a lithium transition metal composite oxide was synthesized in the same manner as in Example B1, and the composite oxide was used in the positive electrode active material to prepare a test battery cell.
[0104] <Example C1>
[0105] [Synthesis of lithium transition metal composite oxide (positive electrode active material)]
[0106] The composite oxide containing Ni and Mn was mixed with lithium hydroxide in such a way that the molar ratio (Li / Me ratio) of Li in lithium hydroxide to the metal element (Me) in the composite oxide was 1:1.030. The mixture was put into a calcining furnace and calcined in two stages. During the calcining process, the mixture was calcined in an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The first heating rate was 2 ° C / min, and the temperature was raised from room temperature to 650 ° C (the first calcination temperature). After that, the second heating rate was 1 ° C / min, and the temperature was raised from 650 ° C to 730 ° C (the second calcination temperature), and maintained at 730 ° C for 5 hours. After the calcined product was crushed, it was washed with water to obtain a lithium transition metal composite oxide (positive electrode active material).
[0107] The lithium transition metal composite oxide was analyzed by ICP-AES, and the composition of the composite oxide was confirmed to be Li 0.99 Ni 0.90 Mn 0.10 O 2 In addition, from the SEM image of the lithium transition metal composite oxide, it was confirmed that the composite oxide was a secondary particle formed by aggregation of primary particles.
[0108] <Example C2>
[0109] Aluminum hydroxide was further added as a raw material of lithium transition metal composite oxide. A lithium transition metal composite oxide was synthesized in the same manner as in Example C1, and the composite oxide was used as a positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.91 Mn 0.04 Al 0.05 O 2 .
[0110] <Example C3>
[0111] Calcium hydroxide was further added as a raw material of lithium transition metal composite oxide. A lithium transition metal composite oxide was synthesized in the same manner as in Example C1, and the composite oxide was used as a positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.88 Mn 0.09 Ca 0.03 O 2 .
[0112] <Example C4>
[0113] Calcium hydroxide and strontium hydroxide were further added as raw materials for lithium transition metal composite oxide. The lithium transition metal composite oxide was synthesized in the same manner as in Example C1, and the composite oxide was used as the positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.87 Mn 0.10 Ca 0.02 Sr 0.01 O 2 .
[0114] <Example C5>
[0115] Aluminum hydroxide, calcium hydroxide and strontium hydroxide were further added as raw materials for lithium transition metal composite oxide. The lithium transition metal composite oxide was synthesized in the same manner as in Example C1, and the composite oxide was used as the positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.89 Mn 0.03 Al 0.05 Ca 0.02 Sr 0.01 O 2 .
[0116] <Comparative Example C1>
[0117] The first heating rate was changed to 5°C / min, the second heating rate was changed to 3°C / min, and the second sintering temperature was changed to 750°C. In addition, a lithium transition metal composite oxide was synthesized in the same manner as in Example C1, and the composite oxide was used in the positive electrode active material to make a test battery cell.
[0118] <Comparative Example C2>
[0119] The first heating rate is changed to 5°C / min, the second heating rate is changed to 3°C / min, and the second sintering temperature is changed to 750°C. In addition, a lithium transition metal composite oxide is synthesized in the same manner as in Example C2, and the composite oxide is used in the positive electrode active material to make a test battery cell.
[0120] <Example D1>
[0121] [Synthesis of lithium transition metal composite oxide (positive electrode active material)]
[0122] The composite oxide containing Ni and Mn was mixed with lithium hydroxide in such a way that the molar ratio (Li / Me ratio) of Li in lithium hydroxide to the metal element (Me) in the composite oxide was 1:1.050. The mixture was put into a calcining furnace and calcined in two stages. During the calcining step, the mixture was calcined in an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The first heating rate was 2°C / min, and the temperature was raised from room temperature to 670°C (the first calcination temperature). Thereafter, the second heating rate was 1°C / min, and the temperature was raised from 670°C to 760°C (the second calcination temperature), and maintained at 760°C for 5 hours. The calcined product was crushed and washed with water to obtain a lithium transition metal composite oxide (positive electrode active material).
[0123] The lithium transition metal composite oxide was analyzed by ICP-AES, and the composition of the composite oxide was confirmed to be Li 0.99 Ni 0.81 Mn 0.19 O 2 In addition, from the SEM image of the lithium transition metal composite oxide, it was confirmed that the composite oxide was a secondary particle formed by aggregation of primary particles.
[0124] <Example D2>
[0125] Calcium hydroxide was further added as a raw material of lithium transition metal composite oxide. A lithium transition metal composite oxide was synthesized in the same manner as in Example D1, and the composite oxide was used as a positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.80 Mn 0.18 Ca 0.02 O 2 .
[0126] <Example D3>
[0127] Calcium hydroxide and strontium hydroxide were further added as raw materials for lithium transition metal composite oxide. The lithium transition metal composite oxide was synthesized in the same manner as in Example D1, and the composite oxide was used as the positive electrode active material to prepare a test battery cell. By ICP-AES, it was confirmed that the composition of the positive electrode active material was Li 0.99 Ni 0.80 Mn 0.17 Ca 0.02 Sr 0.01 O 2 .
[0128] <Comparative Example D1>
[0129] The first heating rate was changed to 5°C / min, the second heating rate was changed to 3°C / min, and the second sintering temperature was changed to 800°C. In addition, a lithium transition metal composite oxide was synthesized in the same manner as in Example D1, and the composite oxide was used in the positive electrode active material to prepare a test battery cell.
[0130] For each test battery cell of the above-mentioned embodiments and comparative examples, a cycle test was carried out, and the capacity retention rate after the test was evaluated. The evaluation results are shown in Tables 1 to 4 together with the physical properties of the positive electrode active material. The capacity retention rate shown in each table is a relative value when the capacity retention rate of the test battery cell of Comparative Example 1 in each table is set to 100. In addition, according to the nanobeam electron diffraction method using TEM, for the positive electrode active material in the cycle test, the crystal structure in the surface layer of the primary particles existing on the surface of the secondary particles was analyzed, and the average thickness of the rock salt structure (NiO phase) and the spinel structure was measured.
[0131] [Evaluation of capacity maintenance rate after cycle test]
[0132] For the above test battery cell, under a temperature environment of 25°C, constant current charging was performed at a constant current of 0.3C until the battery voltage reached 4.2V, and constant voltage charging was performed at 4.2V until the current value reached 0.02C. Thereafter, constant current discharge was performed at a constant current of 0.5C until the battery voltage reached 2.5V. This charge and discharge cycle was performed 500 times. The discharge capacity of the first cycle and the discharge capacity of the 500th cycle of the cycle test were obtained, and the capacity retention rate was calculated according to the following formula.
[0133] Capacity retention rate (%) = (discharge capacity at the 500th cycle ÷ discharge capacity at the 1st cycle) × 100
[0134] [Table 1]
[0135]
[0136] [Table 2]
[0137]
[0138] [Table 3]
[0139]
[0140] [Table 4]
[0141]
[0142] As shown in Tables 1 to 4, the test battery cells of the embodiments have higher capacity retention rates after cycle tests and better cycle characteristics than the test battery cells of the comparative examples. That is, when a composite oxide (Z) having a rock salt structure, a spinel structure, and a layered rock salt structure formed on the surface of specific primary particles is used as a positive electrode active material, the cycle characteristics are greatly improved compared to the case where a positive electrode active material that does not form a spinel structure is used. This effect was confirmed for any of the NCA-based active materials containing Ni, Co, and Al and the NCM-based active materials containing Ni, Co, and Mn.
[0143] In addition, from the results shown in Tables 1 to 4, it is understood that the thickness of the rock salt structure and the spinel structure, especially the thickness of the spinel structure, and the presence or absence of addition of Ca and Sr have a great influence on the cycle characteristics.
[0144] The present disclosure will be further described based on the following embodiments.
[0145] Composition 1:
[0146] A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide containing at least Ni,
[0147] The lithium transition metal composite oxide is a secondary particle formed by aggregation of primary particles, and the primary particles present on the surface of the secondary particles have a crystal structure including a rock salt structure, a spinel structure and a layered rock salt structure formed in sequence from the particle surface.
[0148] Composition 2:
[0149] In the positive electrode active material for a non-aqueous electrolyte secondary battery according to Configuration 1, the average thickness of the spinel structure is 5 nm or less.
[0150] Composition 3:
[0151] In the positive electrode active material for a non-aqueous electrolyte secondary battery according to configuration 1 or 2, the average thickness of the rock salt type structure is 3 nm or less.
[0152] Composition 4:
[0153] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the lithium-transition metal composite oxide contains at least one selected from the group consisting of Ca and Sr.
[0154] Composition 5:
[0155] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the content of Ni in the lithium transition metal composite oxide is 80 mol % or more relative to the total number of moles of metal elements other than Li.
[0156] Composition 6:
[0157] A nonaqueous electrolyte secondary battery comprising: a positive electrode including the positive electrode active material according to any one of configurations 1 to 5, a negative electrode, and a nonaqueous electrolyte.
[0158] Description of Reference Numerals
[0159] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.
Claims
1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide containing at least Ni, The lithium transition metal composite oxide is a secondary particle formed by aggregation of primary particles, and the primary particles present on the surface of the secondary particles have a crystal structure including a rock salt type structure, a spinel type structure and a layered rock salt type structure formed in sequence from the particle surface.
2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The average thickness of the spinel structure is 5 nm or less.
3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The average thickness of the rock-salt type structure is less than 3 nm.
4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide contains at least one selected from Ca and Sr.
5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein In the lithium transition metal composite oxide, the content of Ni is 80 mol % or more relative to the total number of moles of metal elements excluding Li. 6 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material according to claim 1 , a negative electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Positive electrode active material particle
JP2020009562A